Effects of hookah smoking on indoor air quality in homes. Issue 5 (26th October 2016) - Weitzman, Michael; Yusufali, Afzal Hussein; Bali, Fatma; Vilcassim, M J Ruzmyn; Gandhi, Shashank; Peltier, Richard; Nadas, Arthur; Sherman, Scott; Lee, Lily; Hong, Zhang; Shearston, Jenni; Park, Su Hyun; et al.
Abstract : Introduction: Hookahs (water pipes) are rapidly increasing in popularity worldwide. Evidence suggests that although perceived as safer than cigarette smoke, hookah smoke may be as, or even more, dangerous as cigarette smoke. Methods: Air samples from 33 homes—11 where only hookah-smoking occurred, 12 with only cigarettes and 10 with no smoking—were collected to analyse concentrations of particulate matter (PM2.5 ), black carbon, elemental and organic carbon and carbon monoxide (CO). Air quality was assessed in rooms where smoking occurred and in an adjacent room. Results: Hookah and cigarette smoking impaired home air quality. The rooms in which hookahs were smoked showed the highest concentrations for all pollutants. CO was significantly greater in the rooms where hookahs were smoked than in the cigarette-smoking rooms and the non-smoking households (p<0.05). In addition, CO levels in the rooms adjacent to where hookah was smoked were 2.5-fold to 4-fold greater than those in the smoking and non-smoking rooms of the cigarette homes (p<0.05). PM2.5 levels were also elevated in hookah homes compared to cigarette and non-smoking homes, although not significantly different. Conclusions: This study, the first of its kind, demonstrates potentially hazardous levels of home air pollution in rooms where hookahs are being smoked as well as in adjacent rooms. These levels were greater than those in cigarette smoking homes, raising concerns about potential negative health effects on all individuals living in homes where hookahs are smoked.